The Influence of Transformational Leadership, Work Life Balance, and Interpersonal Communication on Job Satisfaction at Puskesmas Muara Pinang - Putri, Syafira Eka; Probosari, Ninik (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the influence of Transformational Leadership, Work-Life Balance, and Interpersonal Communication on Job Satisfaction at Puskesmas Muara Pinang, South Sumatra. This study used a quantitative approach and questionnaire to collect data. This research uses primary data type and measurement scale with Likert scale. A total of 92 respondents in this study were employees of Puskesmas Muara Pinang. This method of human resource analysis represents an important asset that must be considered by using multiple linear regression analysis with SPSS software. The results of this study show that Transformational Leadership, Work Life Balance, and Interpersonal Communication affect Job Satisfaction partially and collectively. Transformational Leadership has the largest beta coefficient variables (0.544), followed by Interpersonal Communication (0.259) and Work Life Balance (0.180). The F-test showed the collective influence of these study variables, with F-statistics 439,202 and significant values of 0.000 showing positive and significant effects. The results of this study show the important role of Transformational Leadership, Work Life Balance, and Interpersonal Communication in improving Job Satisfaction. The Muara Pinang Health Center is recommended to focus on improving the Transformation, Work Balance, and Interpersonal Communication Leadership because this can increase overall job satisfaction.